Experimental investigation of the fracture evolution and fracture criterion of jointed sandstone subject to dry–wet cycling - Zhang, Liang; Wang, Guilin; Liu, Bolong; Sun, Fan; Wang, Ruiqiu (Bulletin of engineering geology and the environment, 2023)
The damage and deterioration of jointed rock mass under dry-wet cycling strongly influence the rock fracture characteristics, which threaten the safety of reservoir bank slopes. To explore the effect of dry-wet cycling on the mechanical properties of jointed rock, in the present study, a sequence of uniaxial compression tests were conducted on the jointed sandstone subject to the dry-wet cycles. The deformation and cracking process were quantitatively studied by the digital image correlation (DIC) system. Subsequently, four failure modes after the dry-wet cycles were found. Finally, a rock fracture criterion that considers the effect of dry-wet cycling is established based on the Drucker-Prager criterion. The results show that the compressive strength, elastic modulus, and crack initiation stress level of the jointed rock samples gradually decreased with increasing dry-wet cycle number. Dry-wet cycling aggravated the localized deformation of the jointed sandstone samples prior to failure and drastically reduced the damage degree during failure. The experiments highlight four main failure modes of jointed rock subjected to dry-wet cycling: tensile failure; mixed shear-tensile failure; buckling-shear failure; and mixed buckling-shear-tensile failure. The fracture toughness calculated using the dry-wet cycle fracture criterion is consistent with that obtained from the fracture test. The established fracture criterion can consequently be applied to estimate the fracture toughness of rock under dry-wet action. This study provides important guidance for the stability analysis of slope rock mass and preventing geological disasters in reservoir bank slopes.